Antiskyrmions and their electrical footprint in crystalline mesoscale structures of Mn1.4PtSn - Winter, Moritz; Goncalves, Francisco J. T.; Soldatov, Ivan; He, Yangkun; Cespedes, Belen E. Zuniga; Milde, Peter; Lenz, Kilian; Hamann, Sandra; Uhlarz, Marc; Vir, Praveen; Koenig, Markus; Moll, Philip J. W.; et al. (Communications Materials, 2022)
Skyrmionic materials hold the potential for future information technologies, such as racetrack memories. Key to that advancement are systems that exhibit high tunability and scalability, with stored information being easy to read and write by means of all-electrical techniques. Topological magnetic excitations such as skyrmions and antiskyrmions, give rise to a characteristic topological Hall effect. However, the electrical detection of antiskyrmions, in both thin films and bulk samples has been challenging to date. Here, we apply magneto-optical microscopy combined with electrical transport to explore the antiskyrmion phase as it emerges in crystalline mesoscale structures of the Heusler magnet Mn1.4PtSn. We reveal the Hall signature of antiskyrmions in line with our theoretical model, comprising anomalous and topological components. We examine its dependence on the vertical device thickness, field orientation, and temperature. Our atomistic simulations and experimental anisotropy studies demonstrate the link between antiskyrmions and a complex magnetism that consists of competing ferromagnetic, antiferromagnetic, and chiral exchange interactions, not captured by micromagnetic simulations.
CRIS-Team Scopus Importer:2023-03-20